2011
DOI: 10.1126/science.1201475
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Sustain Adipose Alternatively Activated Macrophages Associated with Glucose Homeostasis

Abstract: Eosinophils are associated with helminth immunity and allergy, often in conjunction with alternatively activated macrophages (AAMs). Adipose tissue AAMs are necessary to maintain glucose homeostasis and are induced by the cytokine interleukin-4 (IL-4). Here, we show that eosinophils are the major IL-4-expressing cells in white adipose tissues of mice, and, in their absence, AAMs are greatly attenuated. Eosinophils migrate into adipose by an integrin-dependent process and reconstitute AAMs through an IL-4/IL-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
1,350
3
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,208 publications
(1,417 citation statements)
references
References 25 publications
51
1,350
3
13
Order By: Relevance
“…Using a strain of IL-4 reporter mice, Molofsky et al reported that more than 85% of the IL-4-producing cells in lean AT are eosinophils, immune cells that are dependent on IL-5 and IL-13 for growth and survival (12). Mice lacking eosinophils develop severe HFD-induced obesity and insulin resistance and have significantly lower numbers of M2 macrophages (12). iNKT cells resident in AT are also a major source of IL-4.…”
Section: Immune Cell Composition In Lean Atmentioning
confidence: 99%
“…Using a strain of IL-4 reporter mice, Molofsky et al reported that more than 85% of the IL-4-producing cells in lean AT are eosinophils, immune cells that are dependent on IL-5 and IL-13 for growth and survival (12). Mice lacking eosinophils develop severe HFD-induced obesity and insulin resistance and have significantly lower numbers of M2 macrophages (12). iNKT cells resident in AT are also a major source of IL-4.…”
Section: Immune Cell Composition In Lean Atmentioning
confidence: 99%
“…Eosinophils are located in visceral adipose tissue, and the loss of eosinophils leads to a decrease in alternatively activated macrophage (AAM) accumulation [2]. AAMs in gonadal adipose tissue (GAT) are maintained by IL-4 and/or IL-13 [3]. The activation of eosinophils critically depends on IL-5: studies using il5-tg mice or il5-deficient mice and anti-IL-5 Ab have demonstrated that the expansion of eosinophils is largely regulated by IL-5 [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils also play critical roles in metabolic homeostasis relating to obesity [2]. GATA-1 is critical to eosinophil development, and dblGATA mice, in which the GATA binding sites in the Gata1 promoter are mutated, are prone to obesity when fed a high-fat diet [2,3]. Eosinophils are located in visceral adipose tissue, and the loss of eosinophils leads to a decrease in alternatively activated macrophage (AAM) accumulation [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations